Community Intervention Program Of Sukajaya Village, Sumedang Regency Towards Participatory-Based Online Gambling Prevention - Ani Purwati; Cakra Heru Santosa; Rahmi Erwin; Bita Isranti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Online gambling has become a complex social problem in Sukajaya Village, Sumedang, with negative impacts on the economy, mental health, and social stability of the community. Laws and regulations related to online gambling, such as Law Number 19 of 2016 concerning Information and Electronic Transactions (ITE) and the Criminal Code, regulate the prohibition and sanctions against gambling practices. The percentage between ideal norms in regulations and the implementation of reality is still a challenge in prevention and handling efforts. This study aims to develop a participatory-based intervention program in dealing with online gambling behavior through the involvement of the community, village government, and NGOs. The discussion includes identification of causal factors, evaluation of regulatory effectiveness, and design of community-based prevention strategies. The intervention program to suppress online gambling behavior in Sukajaya Village uses a participatory-based approach in the form of educational workshops, legal counseling, and the formation of support groups for affected individuals. The expected results of this study are increased public awareness of the dangers of online gambling, the formation of social support mechanisms, and policy recommendations that are more adaptive to community needs. This study contributes to building effective intervention strategies to create a healthier social environment free from the influence of online gambling. The methods used include workshops, legal counseling, and the formation of support groups for individuals affected by online gambling. In addition, this study explores existing legal regulations related to online gambling to provide a clear framework for prevention efforts. The results of this program are expected to increase public awareness of the dangers of online gambling, strengthen social solidarity, and provide support for individuals experiencing addiction problems. This study is important as a preventive effort in building a healthier and more productive society.